Text messages to increase attendance to follow-up cervical cancer screening appointments among HPV-positive Tanzanian women (Connected2Care): study protocol for a randomised controlled trial - Linde, Ditte S. (Trials, 2017)
BACKGROUND: Cervical cancer is a major health concern in Tanzania, caused by poor attendance for cervical cancer screening and follow-up of women at risk. Mobile telephone health interventions are proven effective tools to improve health behaviour in African countries. So far, no knowledge exists on how such interventions may perform in relation to cervical cancer screening in low-income settings. This study aims to assess the degree to which a Short Message Service (SMS) intervention can increase attendance at appointments among women who have tested positive for high-risk (HR) Human Papillomavirus (HPV) during cervical cancer screening. METHODS/DESIGN: Connected2Care is a non-blinded, multicentre, parallel-group, randomised controlled trial. Tanzanian women testing positive to HR HPV at inclusion are randomly assigned in an allocation ratio of 1:1 to the SMS intervention or the control group (standard care). In a period of 10 months, the intervention group will receive 15 one-directional health educative text messages and SMS reminders for their appointment. The total sample size will be 700 with 350 women in each study arm. Primary outcome is attendance rate for follow-up. Secondary objectives are cost-effectiveness, measured through incremental ratios, and knowledge of cervical cancer by a 16-item true/false scale questionnaire at baseline and follow-up. Barriers against implementing the intervention will be assessed in a mixed-methods sub-population study. DISCUSSION: This study may provide information on the potential effects, costs, and barriers in implementing an SMS intervention targeting a group of women who are followed up after testing positive for HR HPV and are, therefore, at increased risk of developing cervical cancer. This can guide decision-makers on the effective use of mobile technology in a low-income setting. Trial status: recruiting. TRIAL REGISTRATION: ClinicalTrials.gov, ID: NCT02509702. Registered on 15 June 2015. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13063-017-2215-x) contains supplementary material, which is available to authorized users.